Sarcomatoid Carcinoma Of The Mediastinal : A Rare Case of Giant Mass Thymic Carcinoma Subtype - Santoso, Agus Andreas; Parsama Putra, Ngakan Putu; Setiawan, Ungky Agus; Isharanto, Artono; Erawati, Dini Rachma; Yudhanto, Hendy Setyo (Universitaas Brawijaya, 2021)
ABSTRACTTitle: Sarcomatoid Carcinoma Of The Mediastinum: A Rare Case of Giant Mass Thymic Carcinoma SubtypeAuthor: Agus Andreas Santoso, MD. Pulmonology and Respiratory Medicine Department, Brawijaya University, Malang, Indonesia. Supervisor: Ngakan Putu Persama Putra, MD, Pulmonologist Consultant, Ungky Agus Setiawan, MD, Pulmonologist Consultant, Artono I, MD, Cardiovascular and Thorax Surgeon, Dini Rachma Erawati, MD, Radiologist Consultant, Hendy Setyo Yudhanto, MD, Pathology Anatomy Specialist.Introduction: Sarcomatoid carcinoma is a type of thymus carcinoma that contains partial or complete spindle cells. Incidence of Sarcomatoid Carcinoma 5-10% of all patients with thymic carcinoma. Carcinoma Sarcomatoid is a highly progressive tumor, most patients will die after 3 years of diagnosis despite aggressive multimodality therapy.Case Description: A 47-year-old woman with chest pain, shortness of breath, coughing, weight loss, enlarging lump in the neck and chest was felt for 1 month. Physical and supporting examination showed anterior superior mediastinal tumors and soft mass tissue in the right region of the Colli. Based on the Transthoracal FNAB Guiding ultrasound and FNAB the anterior colli region concluded that Thymoma, thyroid oncocytic adenoma and Nodular colloid goiter with azkanasy cell proliferation. The patient had Partial Sternotomy (Hemiclamshell), thymectomy with the final diagnosis of Sarcomatoid Carcinoma. Discussion: Sarcomatoid carcinoma is a type of thymic carcinoma that has both malignant epithelium (carcinomatous) and spindle cells (sarcomatous/sarcomatoid), generally with a transition between the two. This case was interesting because of the rare occurrence of Sarcomatoid Carcinoma plus the large size of tumor mass in this patient.